2015
DOI: 10.4103/0250-474x.164776
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-related prevalence and drug utilization pattern in the management of type 2 diabetes mellitus and its comorbidity with cardiovascular diseases: A comparative study

Abstract: A cross-sectional study of 250 cases of type 2 diabetes management was conducted in a governmental tertiary care hospital of urban south India to determine the comparative prevalence of type 2 diabetes and its comorbidity with cardiovascular diseases in diabetic population, core drug use indicators and drug utilization pattern in the management of diabetics entirely and with cardiovascular diseases. Highest prevalent age group for type 2 diabetes/cardiovascular diseases (greater incidence in female than male) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Regarding gender, the IDF mentions that T2D is more common in men worldwide, but in South and Central America the prevalence is higher in women [1]. Among comorbidities, the association between T2D and hypertension is well known, as are the abuse of alcohol and dyslipidemia, as well as BMI and WC above normal range, regardless of gender or age [18,[20][21][22][23]. Obesity, especially central obesity, is a key factor in the pathophysiology of insulin resistance and diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, the IDF mentions that T2D is more common in men worldwide, but in South and Central America the prevalence is higher in women [1]. Among comorbidities, the association between T2D and hypertension is well known, as are the abuse of alcohol and dyslipidemia, as well as BMI and WC above normal range, regardless of gender or age [18,[20][21][22][23]. Obesity, especially central obesity, is a key factor in the pathophysiology of insulin resistance and diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…No attempt is made to affect the outcome (for example, no treatment is given) 1 . Epidemiological studies have played an important part in the elucidation of predisposing factors for COPD, CKD, acute pancreatitis and CLD and opportunities for prevention and treatment 2 .…”
mentioning
confidence: 99%
“…Furthermore, it has also been observed that various parts of Echium species could be used for their antiinflammatory, antibacterial, antidepressant, antiproliferative, antiviral, antioxidant, cytotoxic and anxiolytic properties [2,3] . Cyanidin, a natural phenolic compound is present in many kinds of plants, such as grapes, pomegranate and some species of Boraginaceae and according to the previous reports, this effective compound has antioxidant and antidiabetic potential [7][8][9][10] .Diabetes mellitus is a common endocrine disease and a leading cause of morbidity and mortality in the world [11] . In this disease, the macro and microvascular complications lead to severe effects on the eyes, central nervous systems and kidneys [12] .…”
mentioning
confidence: 99%
“…Evidence from in vitro and in vivo experiments indicated that diabetic hyperglycemia could increase the risk of complications [13,14] . It seems that non-enzymatic glycation plays an important role in progression of diabetic complications [11] . Due to prolonged hyperglycemia, the non-enzymatic glycation of proteins could significantly change their structural and functional properties [12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation